استحداث الدراسات البينية في أبحاث الجامعات الليبية - الشتيويد. حسين فرج; الرماليد. أمان محمد (Aljameai, 2026)
المستخلص: تستعرض هذه الورقة تجربة تطبيقية رائدة في بعض الجامعات الليبية هدفت إلى تعزيز التكامل بين فروع العلوم التطبيقية ومختلف حقول المعرفة، من خلال تبني منهجية عملية لتجسير الفجوة بين التخصصات. وقد انطلقت هذه التجربة منذ عام 2006 كمبادرة مبتكرة في الربط بين العلوم لإجراء بحوث علمية تطبيقية، دون أن تصنف حينها ضمن مفهوم “الدراسات البينية” بصيغته المعاصرة. وركزت التجربة على تنفيذ مشاريع بحثية تطبيقية في كليات العلوم والصحة والتقنية خلال الفترة (2006–2025)، حيث تم دمج تخصصات متعددة في إطار تكاملي يتجاوز التعاون الأكاديمي التقليدي نحو شراكات أكاديمية-صناعية تهدف إلى تقديم حلول عملية لمشكلات المجتمع. وتعرض الورقة المنهجية المعتمدة في هذا السياق، إلى جانب نتائج تطبيق أربع دراسات بينية تم تنفيذها عبر مشاريع طلابية مشتركة بين أقسام وكليات وجامعات ليبية مختلفة. أظهرت النتائج قدرة هذه التجربة على تجاوز الفجوات البحثية بين التخصصات، وتحقيق تكامل معرفي فعال على مدى تسعة عشر عامًا، مع تطوير تدريجي للمنهجية المتبعة. كما بينت أن التحديات الإدارية والتمويلية لم تعق مسار التنفيذ، بل تم التعامل معها بمرونة أسهمت في استدامة التجربة. وقد حظيت مخرجات هذه التجربة باهتمام متزايد من الجامعات الليبية، باعتبارها نموذجًا واعدًا لتطوير البحث العلمي، خاصة على مستوى الدراسات العليا. وتخلص الورقة إلى أهمية تبني الدراسات البينية كمدخل استراتيجي لتعزيز التكامل المعرفي، وتجاوز الحواجز التقليدية بين التخصصات، بما يسهم في تحسين جودة المخرجات البحثية وخدمة قضايا التنمية. Abstract: This paper presents a pioneering applied experience in selected Libyan universities aimed at enhancing integration among applied sciences and various fields of knowledge through a practical methodology designed to bridge disciplinary gaps. Initiated in 2006, this experience emerged as an innovative approach to linking scientific disciplines for conducting applied research, although it was not explicitly defined at the time as “interdisciplinary studies” in its contemporary sense. The experience focused on implementing applied research projects within faculties of science, health, and technology during the period (2006–2025). These projects integrated multiple disciplines within a collaborative framework that moved beyond traditional academic cooperation toward academic–industrial partnerships, aiming to develop practical solutions to societal challenges. The paper outlines the adopted methodology and presents the outcomes of four interdisciplinary studies conducted through joint student projects across different departments, faculties, and Libyan universities. The findings demonstrate the effectiveness of this experience in bridging research gaps between disciplines and achieving meaningful knowledge integration over nineteen years, supported by a progressively developed methodology. Despite administrative and financial challenges, the experience proved resilient and sustainable. The outcomes have attracted increasing interest from Libyan universities as a promising model for advancing research, particularly at the graduate level. The paper strongly advocates for adopting interdisciplinary approaches as a strategic pathway to enhance knowledge integration, overcome traditional disciplinary barriers, and improve research quality in support of national development.